A emergência do conceito de universidade verde na UFSM, campus Frederico Westphalen - Kempka, Solange Busanello (2016)
This study is focused on the theme of sustainability in universities. The objective was to analyze sustainability practices and the emergence of the Green University concept at UFSM, Campus of Frederico Westphalen. This is a qualitative study with exploratory and descriptive character. The theoretical framework was developed on the topics: Green University, Environmental Education and Environmental Management. Data collection occurred in the second semester of 2015 and was developed in three phases: interviews, documentary analysis and observation. Interviews were conducted with the coordinators of all undergraduate courses and the graduate course coordinator, the representative of the UFSM Environmental Planning Commission in the Campus, the Director and a Professor who performs and participates in actions and activities related to sustainability on campus were also interviewed. The documents analyzed were the UFSM PDI and Projects at UFSM, Campus Frederico Westphalen, which relate in some way to sustainability and had their record in the SIE database, in which 43 projects were located. Four observations of actions at the Campus that were related to the theme of sustainability occurred, as well as photographic record of sustainability practices to complement the data and information obtained. For data analysis, we used the Content Analysis Method. The main evidence indicates that in all categories and subcategories analyzed there are sustainability initiatives being developed. It was found, after analysis of collected data, that the dimensions of Social Responsibility Projects, PPCs, Waste, Campus Preservation and Water are the ones that stand out, that is, they can be considered the practices that are emerging from the Green University concept. But even in these dimensions what is seen are sustainability actions, a plan or strategic planning of short, medium and long term aimed at the overall sustainability of the campus was not identified at any time. The dimensions of Energy, Transport and Purchasing showed greater weakness in relation to sustainability because they have few sustainable actions and practices, however these dimensions also have sustainable actions, but they need further attention.